2010
DOI: 10.1007/s10750-010-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of ostracodes (Ostracoda, Crustacea) in western Mongolia

Abstract: Aquatic biota in Central Asia witnesses and faces a changing environment. Because ostracodes contribute to both extant and fossil lacustrine diversity, they can be used to track evolution in water quality. Living ostracode communities in a variety of aquatic habitats of western Mongolia were analyzed in relation to environmental and hydrochemical variables of those habitats, based on presence/absence data from net samples. The sampled water bodies represent broad gradients in ionic concentration and compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Thus, such results cannot be generalized at the moment. Similar to some of the previous studies (e.g., Sar, 2007;Van der Meeren et al, 2010;Szlauer-Łukaszewska, 2014;Uc¸ak et al, 2014), four species (I. inermis, I. bradyi, H. incongruens and D. stevensoni) are located relatively closer to the centre of diagram (Fig. 3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, such results cannot be generalized at the moment. Similar to some of the previous studies (e.g., Sar, 2007;Van der Meeren et al, 2010;Szlauer-Łukaszewska, 2014;Uc¸ak et al, 2014), four species (I. inermis, I. bradyi, H. incongruens and D. stevensoni) are located relatively closer to the centre of diagram (Fig. 3).…”
Section: Discussionsupporting
confidence: 88%
“…They inhabit a variety of aquatic bodies ranging from fresh to saline waters (e.g., lakes, troughs (like narrow canal designed to hold water), ponds, springs, caves) (Delorme, 1991;Yavuzatmaca et al, 2012;Ku¨lko¨ylu¨og˘lu et al, 2013) and are used as bio-indicator of water quality (Delorme, 1991). Published studies are available describing ostracod habitat preferences (Benzie, 1989;Du¨gel et al, 2008), habitat similarities (Sar and Ku¨lko¨ylu¨og˘lu, 2010), and ecology and distribution (Teeter, 1973;Malmqvist et al, 1997;Mezquita et al, 1999;Kiss, 2007;Pieri et al, 2009;Van der Meeren et al, 2010;Ku¨lko¨ylu¨og˘lu et al, 2013). However, with the exception of Heip (1976), there is no specific research on the distributional patterns of ostracods using Poisson probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the type locality, it was also reported from a lake in western Mongolia (Van der Meeren et al, 2010). In the present study, a dense bisexual population was found in site X36 of Inner Mongolia, and several females were also found at site X4 (table I).…”
Section: Resultssupporting
confidence: 76%
“…Since only a limited number of variables were measured in the present study, other, unmeasured factors could have even more pronounced effects in this category (for example nutrients by Van der Meeren et al, 2010). Higuti et al (2009c), however, showed that hydrodynamic fluctuations of systems and habitats are more important to darwinulid distribution than abiotic variables of the water bodies.…”
Section: Effects Of Other Variablesmentioning
confidence: 80%
“…Comparable surveys have yielded comparable diversities: 47 ostracod species from 33 European lakes (Viehberg, 2006), 29 species from 36 Canadian lakes (Bunbury & Gajewski, 2005), 30 species from 100 lakes in Tibet (Mischke et al, 2007) and 47 species from 106 samples in Western Mongolia (including lakes, springs, streams and pools) ( Van der Meeren et al, 2010). Yet, this is less than one could have expected and this for several reasons.…”
Section: Diversitymentioning
confidence: 99%